Development and Storage Stability of Whey Sugarcane Based Functional Beverage - Qamar U Zaman; Amna Sahar; Aysha Sameen; Muhammad Haseeb Ahmad; Niaz Muhammad; Nuzhat Huma; Muhammad Faizan Afzal; Waseem Khalid; Ammar Al-Farga (International Journal of Food Properties, 2023)
Whey and sugarcane juice contain many functional components like immunoglobulins and antioxidants, which are very beneficial for human health. Pakistan is the world’s 4th and 5th largest producer of milk and sugarcane, but we are still importing dairy products and sugar from foreign countries. Using whey and sugarcane juice to make value-added functional drinks can enhance its consumption and ultimately be exported to foreign markets. In this research, sugarcane juice was incorporated in whey in five different Blends; 10, 20, 30, 40, and 50%. The product was subjected to different physicochemical analyses at 0-day, 7-day, 14 days, 21 days and 28 days of storage. Results were analyzed through two-way factorial under CRD, which indicated that there was a highly significant effect (p < .01) of blends on all the proximate analyses (fat, protein, total solids, and ash) of the product, while the effect of storage (days) was non-significant (p > .05). Moreover, the interaction effect (Blends*storage days) was non-significant (p > .05) on all the test parameters. However, the individual effect of days and Blends on other physiochemical tests; pH, acidity (%), sedimentation (%), viscosity (c.p), and antioxidants (µg/mL) was highly significant (p < .01). While density (g/ml) and total phenolic contents were significantly affected (p < .01) by Blends with a non-significant (p > .05) effect of storage (days). Apart from that, the sensory analysis indicated that all the parameters were affected by both Blends and storage (days) with a highly significant effect (p < .01). Conclusively this whey-based sugar cane beverage is an innovative and newly emerged functional drink with a lot of nutrition and health-promoting effects. However, it needs further research to evaluate the proper storage conditions and the use of different preservatives to enhance its keeping quality.